Fekalna transplantacija i infekcija Clostridioides difficile - Knežević, Darija; Petković, Miroslav (Scripta Medica, 2021)
Faecal microbiota transplantation (FMT), known equally well as faecal transplanta- tion or faecal bacteriotherapy, is the process of implanting the faecal suspension con- taining balanced microbiota from a healthy donor to the colon of a recipient patient. Excessive growth of Clostridioides difficile (C difficile) in the intestinal microbiota re- sulting from antibiotic consumption is currently a rising threat to public health. FMT is one of the most important, newer approaches to treating C difficile infections. Since C difficile is regarded as an opportunistic bacterium triggering disease in conditions of disturbed homeostasis of the intestinal microbiota, restoration of healthy intestinal microflora facilitates suppression of toxic strain of C difficile by anaerobic bacteria of normal intestinal microflora with concomitant cure. Nurses have important role in caring for patients after faecal transplantation.
Keywords: Faecal transplantation; Clostridioides difficile infection; Microbiota